HUBUNGANANTARA KETERAMPILANMOTORIKSISWA DAN INTENSITAS PEMANFAATANMEDIA PEMBELAJARAN DI SEKOLAH DENGANPRESTASI BELAJAR IPA SISWA KELAS V SDNEGERI SE-KECAMATANALIANKABUPATENKEBUMEN TAHUNPELAJARAN2015/2016 - Bagas Mega Widyanto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
This study descriptively aimed to know (1) the category of motoric skill, (2) the category of intensity of the use of teaching media, and (3) the category of leaning achievement of science subject. This study correlatively aimed to know (1) correlation between motoric skill with leaning achievement of science subject, (2) correlation between intensity of the use of teaching media with leaning achievement of science subject, (3) correlation between motoric skill and intensity of the use of teaching media with leaning achievement of science subject among the fifth grade students of state elementary school in Alian District Kebumen in academic year 2015/2016. The type of this study was ex-post facto. Data collecting techniques used questionnaire and documentation. Data analyzing techniques used descriptive technique and hypothesis testing by using double regression with two predictors that was started by normality test and linearity test. This study shows that the correlation coefficient of each independent variable had a positive correlation with dependent variable. The study shows that there was a positive and significant correlation between motoric skill and intensity of the use of teaching mediawith leaning achievement of science subject(R = 0.50 and Freg = 16.42). The score of = 0.24, it means that motoric skill had a positive and very significant correlation with learning achievement of science subject. The score of = 0.37, it means that intensity of the use of teaching media had a positive and very significant correlation with learning achievement of science subject. Based on those results, it could be concluded that that there was a positive and very significant correlation between motoric skill and intensity of the use of teaching mediatogether with leaning achievement of science subject among the fifth grade students of state elementary school in Alian District Kebumen in academic year 2015/2016.